OPTIMASI PROSES PENGERINGAN PADA PEMBUATAN TEPUNG IKAN PENJA TERHADAP KADAR PROTEIN, KADAR GIZI, KADAR AIR DAN RENDEMEN TEPUNG IKAN PENJA - Firdaus Syafii; Hasmar Fajriana (Journal Of Agritech Science (JASc), 2022)
Penja fish is endemic to the waters of West Sulawesi. Penja fish is in great demand because it has many advantages, including being easy to obtain, cheap, tastes good, and a source of protein. However, the processing of penja fish is still traditional as result it is easily damaged and has a short shelf life. One way to improve the quality of penja fish is the drying process to produce flour of penja fish. Flour of Penja fish has many advantages, it has a long shelf life, economical, efficient and has a high protein content. However, an improper drying process can affect the nutritional content of the product therefore it is necessary to optimize drying. This study aims to improve the quality of penja fish by optimizing the drying process in the production flour of penja fish. The experimental design used in this study is the Response Surface Methodology (RSM). The factors used were temperature and time. Responses measured were protein content, calcium content, moisture and yield. The results showed that the optimum point occurred at a temperature of 60 oC and 24 hours which gave response values ​​for protein content (62.32%), calcium content (240.54 mg/100g), moisture (4.12%), and yield (15.21%).